Radiofrequency ablation for the treatment of haemorrhoidal disease: a minimally invasive and effective treatment modality - Eddama, M. M. R. (Tech Coloproctol, 2019)
BACKGROUND: Haemorrhoidal disease (HD) is a common colorectal condition that often requires surgical treatment. Less invasive procedures are usually more acceptable to patients. The aim of this study was to report the outcome of a novel and minimally invasive technique employing a radiofrequency ablation (RFA) energy (Rafaelo(®)) to treat HD. METHODS: A total number of 27 patients who had RFA for the treatment of HD were recruited to this study. The procedure was performed under deep sedation and local anaesthesia. Patients’ demographics; haemorrhoid severity score (HSS); quality of life; pain and satisfaction scores; and recurrence rate were recorded. RESULTS: The mean age of the patients was 46 (SD 14) years, 18 (67%) males and 9 (33%) females. The mean body mass index was 25 (SD 4) kg/m(2). The predominant symptom of all patients was per-rectal bleeding. HSS improved from 7.2 (SD 1.9) before the procedure to 1.6 (SD 1) after the procedure (p < 0.0001). Postoperative pain scores on a scale of 0–10 were 0, 2 (SD 2), 1 (SD 2), and 0 on immediate, day-1, day-3, and 2-month follow-up questionnaire. The mean satisfacion score was 9 (SD 1.5) out of 10 on 2-month follow-up. Mean time until patients returned to normal daily activity was 3 (SD 1) days following the procedure. Quality-of-life assessments including: visual analogue scale scores (before: mean 70, SD 23; after: mean 82, SD 16; p < 0.001) and EQ-5D-5L (before: mean 0.84, SD 0.15; after: mean 0.94, SD 0.13; p < 0.05) were significantly improved. The mean length of follow-up for recurrence of symptoms was 20 months (range 12–32 months). One patient (4%) reported the recurrence of rectal bleeding 12 months after the procedure. CONCLUSIONS: RFA for the treatment of HD is safe and effective in achieving symptomatic relief. It is associated with minimal postoperative pain and low incidence of recurrence.